2020
DOI: 10.3390/healthcare8020096
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Frequent Attenders Compared with Non-Frequent Attenders in Primary Care: Study of Remote Communities in Taiwan

Abstract: Frequent attenders (FAs) have an impact on the medical resources and the quality of care. In Taiwan, the characteristics of FAs remain unclear in primary care. Outpatient data were screened from a central clinic within six surrounding fishing villages in northeastern Taiwan in 2017. FAs were defined as those who made >18 visits in one year, and those who made ≤18 visits were defined as non-frequent attenders (NFAs). Data of FAs and NFAs were collected and compared. The major diagnoses were reported using In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Smits et al concluded that FAs cause exceedingly high costs in not only primary care but also specialist care [ 5 ]. Furthermore, a recent study using data from remote communities in Taiwan indicated that FAs are characterized by higher costs related to prescriptions, therapeutics, and first visit than non-FAs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smits et al concluded that FAs cause exceedingly high costs in not only primary care but also specialist care [ 5 ]. Furthermore, a recent study using data from remote communities in Taiwan indicated that FAs are characterized by higher costs related to prescriptions, therapeutics, and first visit than non-FAs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…These disorders can range from mild to severe and can cause a wide range of symptoms, including fatigue, weakness, and shortness of breath. They can also have significant implications for pregnancy and childbirth, both for the mother and the developing fetus [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Socio-demographic characteristics as well as the individual’s subjective perception of their own health are also associated with an increased likelihood of frequent consultations ( 6 , 7 ). Finally, an analysis of the prescriptions issued during these repeat consultations showed that there is an increased frequency of prescription, for longer durations, and for more expensive drugs ( 8 ).…”
Section: Introductionmentioning
confidence: 99%